2008
DOI: 10.1080/09658210802337734
|View full text |Cite
|
Sign up to set email alerts
|

Providing information about diagnostic features at retrieval reduces false recognition

Abstract: In the following study, participants encoded blocked DRM word lists and we varied whether they received information before test about the utility of mnemonic features that potentially discriminate between veridical and false memories. The results of three experiments revealed that this manipulation successfully reduced false recognition of critical theme words. We also found that this manipulation was effective for younger but not older adults. Furthermore, calling attention to the features in test instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…Although substantial false alarm rates generally persist following warnings, they are usually significantly lower than those of unwarned controls (e.g., Gallo, Roberts, & Seamon, 1997;McDermott & Roediger, 1998). Although some evidence indicates that the warning must be delivered before encoding of the study lists for a reduction in false alarms to occur (e.g., Anastasi, Rhodes, & Burns, 2000;Neuschatz, Payne, Lampinen, & Toglia, 2001), other evidence suggests that a warning delivered between study and test can have a beneficial effect as well (e.g., Lane, Roussel, Starns, Villa, & Alonzo, 2008;McCabe & Smith, 2002;Starns et al, 2007). If, as the latter finding suggests, participants benefit from insight into the test design without having such knowledge at study, the use of this information, and the consequent decrease in critical false alarms, must be achievable via processes operating at test.…”
Section: Methodsmentioning
confidence: 96%
“…Although substantial false alarm rates generally persist following warnings, they are usually significantly lower than those of unwarned controls (e.g., Gallo, Roberts, & Seamon, 1997;McDermott & Roediger, 1998). Although some evidence indicates that the warning must be delivered before encoding of the study lists for a reduction in false alarms to occur (e.g., Anastasi, Rhodes, & Burns, 2000;Neuschatz, Payne, Lampinen, & Toglia, 2001), other evidence suggests that a warning delivered between study and test can have a beneficial effect as well (e.g., Lane, Roussel, Starns, Villa, & Alonzo, 2008;McCabe & Smith, 2002;Starns et al, 2007). If, as the latter finding suggests, participants benefit from insight into the test design without having such knowledge at study, the use of this information, and the consequent decrease in critical false alarms, must be achievable via processes operating at test.…”
Section: Methodsmentioning
confidence: 96%
“…Participants in the forewarned condition received instructions prior to the recognition test, adapted from Lane et al (2008), in which they were informed of the associative nature of the lists and shown an example, given diagnostic information about the types of information that might enhance memory accuracy (e.g., sensory details, the position of the word in a list, and memories of thoughts and reactions experienced in response to a word), and encouraged to use these characteristics to increase accuracy and avoid endorsing unstudied items as old. Participants in the control condition were not forewarned of the DRM illusion and made old/new decisions without remember/know decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, while unbiased lineup instructions generally encourage more conservative response bias, providing specific task-related information about potential errors may preferentially reduce false identifications and increase discriminability (Blank & Launay, 2014;Higham, Blank, & Luna, 2017). Following taskrelated instructions shown to be effective in associative recognition 2008), we informed participants about target-filler similarity, familiarity-based decision-making, and recollection.…”
Section: Modified Lineup Proceduresmentioning
confidence: 99%
“…While task-related instructions alone have been shown to effectively increase discriminability in tasks featuring high target-filler similarity, phenomenological information often contributes to their effect 2008). Phenomenological information directs attention to memory qualities that are indicative of accurate remembering: relative vividness, clarity, and detail (Mather, Henkel, & Johnson, 1997).…”
Section: Modified Lineup Proceduresmentioning
confidence: 99%